2018
DOI: 10.1111/ene.13547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an early respiratory care programme with non‐invasive ventilation adaptation in patients with amyotrophic lateral sclerosis

Abstract: Very early NIV prescription prolongs the free time from diagnosis to death in NB ALS patients whilst tracheotomy reduces the mortality risk in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 28 publications
3
44
0
16
Order By: Relevance
“…[9][10][11] It has also been shown that NIV might also delay respiratory decline. 13,14 In this study, we found an overall median survival of 9.6 months, which is in line with previous publications. 13,14 In this study, we found an overall median survival of 9.6 months, which is in line with previous publications.…”
Section: Ventilation Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…[9][10][11] It has also been shown that NIV might also delay respiratory decline. 13,14 In this study, we found an overall median survival of 9.6 months, which is in line with previous publications. 13,14 In this study, we found an overall median survival of 9.6 months, which is in line with previous publications.…”
Section: Ventilation Parameterssupporting
confidence: 93%
“…>80% might benefit from NIV. 13,14 In this study, we found an overall median survival of 9.6 months, which is in line with previous publications. 15 We did not find a signif- bulbar-onset patients.…”
Section: Recommendations) Even Patients With Forced Vital Capacity (Fvc)supporting
confidence: 93%
“…However, several arguments suggest that early ventilation could reduce the respiratory decline in ALS and decrease respiratory work . A large retrospective study and three small series have demonstrated an improvement in survival for patients initiating NIV with VC > 80% predicted, although this effect was not confirmed when sham NIV was used in the control group . In practice, patients with only minimal respiratory symptoms, essentially presenting features of motor disability, are unlikely to continue long‐term NIV if the therapy is initiated prior to exhibiting hypoventilation.…”
Section: Criteria For Initiation Of Nivmentioning
confidence: 99%
“…A recent retrospective study demonstrated that in a group of ALS patients initiated on NIV very early (i.e., with FVC ≥80%) and for at least 4 h/day or 120 h/month, the survival from symptom onset was significantly longer and the crude death rate was significantly lower compared to those patients initiated to NIV later (i.e., with FVC < 80%) [16, 17]. …”
Section: Rationale and Timing For Niv Applicationmentioning
confidence: 99%
“…Several studies have clearly shown that NIV treatment can prolong survival of NMD patients who accept and tolerate NIV compared to those who do not accept, tolerate or use it [17, 33, 110-115]. …”
Section: Ethical Dilemmasmentioning
confidence: 99%